Evaluation of the productivity of crossbred dairy cattle on smallholder and government farms in the Republic of Malawi - Agyemang, K.; Nkhonjera, L.P. (International Livestock Centre for Africa, 1986)
Reports the results of a study conducted to compare the important reproductive and productive traits of crossbred dairy cattle on smallholder farms and at multiplication and research cnetres at Malawi, to measure the influence of environment on dairy production traits, to assess the suitability of various crosses to the different agricultural areas, and to determine the trends in dairy production over the years.